Growth performance of Shea nut tree (Vitellaria paradoxa) collections in an ex-situ trial plot in Lira District, Uganda. - Okao, Moses; Odoi J.B.; Okia C.A (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
Shea nut tree (Vitellaria paradoxa) is one of the most important indigenous trees growing in sub-Saharan Africa. Its primary product, Shea butter is used to make vital ingredients in confectionary, cosmetic and pharmaceutical industries. Despite its significance, little is known about its progression in growth from germination to maturity. To close this knowledge gap, a study to assess the growth performance was conducted on Shea tree collections from four provenances of Northern Uganda. The objectives of the study were to; establish a collection of V. paradoxa trees from the different major growing areas in Lango sub-region to serve as a genebank for future improvement programmes; compare the growth performance of the different accessions and to bring V. paradoxa into domestication to avoid depletion of those in the wild. The study was designed in a systematic plot design at a spacing of 4 m x 8 m in August, 2011. Minimal growth for all accessions was observed in the first 24 months followed by an abrupt but steady height gain thereafter for 20 months. Accessions from Palabek recorded the greatest height and number of branches; whereas Adwari had the lowest branch recruitment. Significant variations in growth demands for studies to correlate traits investigated with fruit nut yield of the parent trees.